Preserving the Environment for posterity: The roles of Political PartiesEconomists and Social Advocates (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Environmental degradation has beset the whole world especially in recent times manifesting itself in likes of adverse climate, surfeit reduction in natural resources, radical shift in climate change, widespread pollution of air and water, reduction in fauna etc.It is one of the most alarming issues which we, as a collective human race, must come forward to tackle and find solutions for such a predicament of violent changes in the whole environment. The United Nations (UN) has many times adopted numerous resolutions aimed at addressing various environmental problems. These resolutions often play a crucial role in mobilising international cooperation and setting global standards for environmental protection. Several countries have been beset with serious environmental problems including India where the country, as a developing nation, boosts its economy by capitalising on its natural resources and its non-renewable resources. However, such practices are invariably backfiring on the country's sustainability front. The role of political parties is little at the grassroots level, the absence of such is weakening its collective effort to encounter climate issues. Their role is of utmost necessity in tackling environmental problems. This paper studies several environmental problems engulfing the country and establishes the fact that Sustainable development is essential for any country to survive continually and also roots out solutions for the preservation and protection of the environment.